PD-L1 expression as a predictor of postoperative recurrence and the association between the PD-L1 expression and EGFR mutations in NSCLC - Kensuke Kojima (Nature Portfolio, 2021)
Abstract Although information on the PD-L1 expression and EGFR mutations in non-small cell lung cancer (NSCLC) is important for therapeutic strategies, the effect of these factors on postoperative recurrence and the association between each factor have remained unclear. We retrospectively assessed the PD-L1 expression and EGFR mutations in 280 NSCLC patients, and analyzed the associations by multivariate analyses. The hazard ratio (HR) of postoperative recurrence in cases with high (≥ 50%) PD-L1 expression regarding negative expression was 4.83 (95% confidence interval [CI] 1.51–15.5). The HR for the PD-L1 expression, considered a continuous variable, was 1.016 (95% CI 1.01–1.03). The HRs in cases with EGFR major and minor mutations were 0.42 (95% CI 0.14–1.25) and 0.63 (95% CI 0.18–2.15), respectively. The high PD-L1 (≥ 50%) expression was significantly associated with exon 21 L858R mutation (Ex21) of EGFR (odds ratio, 0.10; 95% CI 0.01–0.87). The risk of postoperative recurrence increased 1.016-fold for every 1% increase in the PD-L1 expression, and a marked increase in risk was observed for expression levels of ≥ 50%. Whereas EGFR mutations were not an independent risk factor. The high PD-L1 (≥ 50%) expression was negatively associated with Ex21. These findings may help identify NSCLC patients with an increased risk of postoperative recurrence.